Fifteen new species of Liphanthus Reed (Hymenoptera: Andrenidae) with two submarginal cells - Sharifi, Negar Mir; Graham, Liam; Packer, Laurence (Zootaxa, 2019)
Hitherto, the panurgine genus Liphanthus Reed 1894 has been thought to have only a single species with two, as opposed to three, submarginal cells. Here we describe an additional fifteen species with two submarginal cells. These new species are: L. jenamro Mir Sharifi & Packer, L. sapos Mir Sharifi & Packer, L. domeykoi Packer, L. discolor Mir Sharifi & Packer, L. centralis Mir Sharifi & Packer, L. molavi Mir Sharifi & Packer (all of the above are from Chile), L. abotorabi Mir Sharifi & Packer, L. cochabambensis Mir Sharifi & Packer (both from Bolivia), L. fritzi Mir Sharifi & Packer, L. amblayensis Mir Sharifi & Packer (both from Argentina), L. ancashensis Mir Sharifi & Packer (from Peru), L. tregualemensis Packer (from Chile), L. yrigoyeni Packer, L. sparsipunctus Packer (both from Argentina) and L. aliavenus Packer (from Chile). Only L. tregualemensis readily fits within any of the previously described subgenera—Liphanthus (Leptophanthus) Ruz and Toro 1983. Liphanthus aliavenus is known from two specimens, one with three and one with two submarginal cells whereas L. molavi has one individual with two submarginal cells on one forewing and three on the other while all other specimens have two submarginal cells on each forewing. We verified that none of these new species are merely two submarginal celled variants of species with three submarginal cells (such intraspecific variation arises also in some other bees) by i) comparing each of the new species with all keys, figures and descriptions of all Liphanthus species, ii) comparisons with holotypes and/or paratypes of most of the described species and iii) surveys of the specimens of undescribed species with three submarginal cells in our collection. None of the new species seem closely related to L. (Neoliphanthis) bicellularis Ruz and Toro 1983, the only previously described Liphanthus species with two submarginal cells. It is the second submarginal crossvein that is lost in all species except L. aliavenus in which the first submarginal cross vein is lost. DNA barcode data are presented for some of the species. Some interesting morphological features associated with the penis valves are described and discussed. The genus is recorded from Bolivia for the first time.